Secondary Malignancy Risk Following Proton vs. X-ray Treatment of Mediastinal Malignant Lymphoma: A Comparative Modeling Study of Thoracic Organ-Specific Cancer Risk - König, Laila; Haering, Peter; Lang, Clemens; Splinter, Mona; von Nettelbladt, Bastian; Weykamp, Fabian; Hoegen, Philipp; Lischalk, Jonathan W.; Herfarth, Klaus; Debus, Jürgen; Hörner-Rieber, Juliane (Frontiers in Oncology, 2020)
Purpose: Proton radiotherapy (PRT) is potentially associated with a lower risk for secondary malignancies due to a decreased integral dose to the surrounding organs at risk (OARs). Prospective trials confirming this are lacking due to the need for long-term follow-up and the ethical complexities of randomizing patients between modalities. The objective of the current study is to calculate the risk for secondary malignancies following PRT and photon-based intensity-modulated radiotherapy (IMRT). Materials and Methods: Twenty-three patients (16 female and seven male), previously treated with active scanning PRT for malignant mediastinal lymphoma at Heidelberg Ion Beam Therapy Center, were retrospectively re-planned using helical photon IMRT. The risk for radiation-induced secondary malignancies was estimated and evaluated using two distinct prediction models (1–4). Results: According to the Dasu model, the median absolute total risk for tumor induction following IMRT was 4.4% (range, 3.3–5.8%), 9.9% (range, 2.0–27.6%), and 1.0% (range, 0.5–1.5%) for lung, breast, and esophageal cancer, respectively. For PRT, it was significantly lower for the aforementioned organs at 1.6% (range, 0.7–2.1%), 4.5% (range, 0.0–15.5), and 0.8% (range, 0.0–1.6%), respectively (p ≤ 0.01). The mortality risk from secondary malignancies was also significantly reduced for PRT relative to IMRT at 1.1 vs. 3.1% (p ≤ 0.001), 0.9 vs. 1.9% (p ≤ 0.001), and 0.7 vs. 1.0% (p ≤ 0.001) for lung, breast, and esophageal tumors, respectively. Using the Schneider model, a significant risk reduction of 54.4% (range, 32.2–84.0%), 56.4% (range, 16.0–99.4%), and 24.4% (range, 0.0–99.0%) was seen for secondary lung, breast, and esophageal malignancies, favoring PRT vs. X-ray-based IMRT (p ≤ 0.01). Conclusion: Based on the two prediction models, PRT for malignant mediastinal lymphoma is expected to reduce the risk for radiation-induced secondary malignancies compared with the X-ray-based IMRT. The young age and the long natural history of patients diagnosed with mediastinal lymphoma predisposes them to a high risk of secondary malignancies following curative radiotherapy treatment and, as a consequence, potentially reducing this risk by utilizing advanced radiation therapy techniques such as PRT should be considered.